Changes in taxonomic and functional diversity of fish communities after catastrophic habitat alteration caused by construction of Three Gorges Dam. Issue 12 (28th April 2020) - Zhang, Chen; Fujiwara, Masami; Pawluk, Michaela; Liu, Huanzhang; Cao, Wenxuan; Gao, Xin
Abstract: Habitat alterations that result from anthropogenic disturbance impact both the abiotic and biotic conditions of ecosystems, causing changes in biodiversity in many parts of the world. Recently, the use of functional diversity has been suggested as an approach to better evaluate the effects of such disturbance on particular communities. Here, we investigated the temporal changes in species and functional diversities of fish communities in the downstream area of the Three Gorges Dam (TGD) before, during, and after impoundment. We found two regime shifts in the fish community in 2004 and 2013 following impoundment. Although taxonomic diversity declined sharply at the first regime shift, it increased at the second shift. On the other hand, functional diversity declined throughout the same period, indicating the loss of functional diversity despite increased species diversity. Our analysis also showed that the fish communities shifted from under‐dispersion to over‐dispersion due to both a decrease in the relative abundance of migratory fish and an increase in the number of fish adapted to the new hydrologic conditions. Our results indicated that the impacts of dams on downstream fish communities may change over time. Interactions between species may become more important when the environment is stable. Abstract : We investigated the temporal changes in taxonomic and functional diversities of fish communities in the downstream area of the Three Gorges Dam (TGD).We found two regime shifts in the fish community and the opposite trends in taxonomic and functional diversities.